Clinical survival and performance of premolars restored with direct or indirect cusp-replacing resin composite restorations with a mean follow-up of 14 years. Issue 4 (April 2023) - Hofsteenge, JW; Fennis, W.M.M.; Kuijs, R.H.; Özcan, M.; Cune, M.S.; Gresnigt, M.M.M.; Kreulen, C.M.
Abstract: Objectives: The objective is to evaluate the long-term clinical survival and performance of direct and indirect resin composite restorations replacing cusps in vital upper premolars. Methods: Between 2001 and 2007, 176 upper premolars in 157 patients were restored with 92 direct and 84 indirect resin composite restorations as part of an RCT. Inclusion criteria were fracture of the buccal or palatal cusp of vital upper premolars along with a class II cavity or restoration in the same tooth. Results: Forty patients having 23 direct and 22 indirect composite restorations respectively, were lost to follow-up (25.6%). The cumulative Kaplan-Meier survival rates were 63.6% (mean observation time: 15.3 years, SE 5.6%) with an AFR of 2.4% for direct restorations and 54.5% (mean observation time: 13.9 years, SE: 6.4%) with an AFR of 3.3% for indirect restorations. The Cox regression analysis revealed a statistically significant influence of the patient's age at placement on the survival of the restoration (HR 1.036, p = 0.024), the variables gender, type of upper premolar, type of restoration, and which cusp involved in the restoration had no statistically significant influence. Direct composite restorations failed predominantly due to tooth fracture, indirect restorations primarily by adhesive failure (p < 0.05). Significance: There was no statistically significant difference in survival rates between direct and indirect composite cusp-replacing restorations. Both direct and indirect resin composite cusp-replacing restorations are suitable options to restore compromised premolars. The longer treatment time and higher costs for the indirect restoration argue in favor of the direct technique.